HUBUNGAN EFIKASI DIRI TERHADAP MOTIVASI BELAJAR FISIKA SISWA - Siregar, Irdes Hidayana; Sartika, Sartika; Nasution, Eni Sumanti (Institut Agama Islam Negeri Padangsidimpuan, 2024)
This research aims to determine the positive and significant relationship between self-efficacy and physics learning motivation for class VII students at SMP Negeri 7 Natal Satu Roof. The formulation of the problem in the research carried out is whether there is a positive and significant relationship between self-efficacy and motivation to learn physics in class VII of SMP Negeri 7 Natal Satu Roof. This research method uses quantitative research with correlation research. The sample used was 29 students at SMP Negeri 7 Natal Satu Roof. The instruments used for self-efficacy and learning motivation used a questionnaire with a Likert scale. Data analysis techniques used normality tests, homogeneity tests, linearity tests. And hypothesis testing uses the correlation test. The results of the research show that there is a positive and significant relationship between self-efficacy and learning motivation of class VII students at SMP Negeri 7 Natal Satu Roof. This can be shown by the correlation value of 0.444 between self-efficacy and motivation to learn physics in class VII students of SMP Negeri 7 Satu Atap Batang Natal, Mandailing Natal Regency, while the significant value is 0.038 which shows a positive relationship.